Process analysis in the implementation of educational programs work education - Delgado, Teresa Acosta
This study addressed the Process Analysis in the Implementation of Educational Programs: Work Education. The findings indicated that the goals and objectives of Work Education, as perceived by both the administrators and teachers of the four case schools are compatible with and supportive of the philosophy behind Work Education. It was stated that the alternatives or courses of action taken in order to achieve Work Education goals and objectives exhibited slight variations and/or differences. The researcher concluded that the implementation of Work Education in the primary grades is inexpensive in comparison with the cost of implementing the same educational program in the secondary grades.